Distinct EpCAM-Positive Stem Cell Niches Are Engaged in Chronic and Neoplastic Liver Diseases - Safarikia, Samira; Carpino, Guido; Overi, Diletta; Cardinale, Vincenzo; Venere, Rosanna; Franchitto, Antonio; Onori, Paolo; Alvaro, Domenico; Gaudio, Eugenio (Frontiers in Medicine, 2020)
In normal human livers, EpCAMpos cells are mostly restricted in two distinct niches that are i) bile ductules, and ii) the mucous glands present inside of the wall of large intrahepatic bile ducts (the so-called peribiliary glands). These EpCAMpos cell niches have been proven to harbor stem/progenitor cells with great importance in liver and biliary tree regeneration and in the pathophysiology of human diseases. The EpCAMpos progenitor cells within bile ductules are engaged in driving regenerative processes in chronic diseases affecting hepatocytes or interlobular bile ducts. The EpCAMpos population within peribiliary glands is activated when regenerative needs are finalized to repair large intra- or extra-hepatic bile ducts affected by chronic pathologies, including primary sclerosing cholangitis and ischemia-induced cholangiopathies after orthotopic liver transplantation. Finally, the presence of distinct EpCAMpos cell populations may explain the histological and molecular heterogeneity characterizing cholangiocarcinoma, based on the concept of multiple candidate cells of origin. This review aimed to describe the precise anatomical distribution of EpCAMpos populations within the liver and the biliary tree and to discuss their contribution in the pathophysiology of human liver diseases, as well as their potential role in regenerative medicine of the liver.